Clinical Case of Rare Hereditary Pathology - Klippel-Trenaunay-Weber-Rubashov Syndrome in Pediatrician's Practice - A.A. Konyushevskaya; S.Ya. Yaroshenko (Zaslavsky O.Yu., 2014)
The article deals with the study of clinical and morphological features of Klippel-Trenaunay-Weber-Rubashov syndrome (cutaneous angiomas, superficial veins dilatation, hypertrophy of affected extremity, arteriovenous anastomoses). The data about the nature, pathogenetic mechanisms, the prevalence of the syndrome are given, a typical clinical case is considered.